Nature's great events - Bass, Karen (Chicago ; London : University of Chicago Press, 2009)
In this companion book to the television series, six of the most spectacular natural phenomena on our planet are explored--the flooding of the Okavango Delta in Botswana; the melting of 10 million square kilometers of ice in the Arctic; the migration of the Serengeti; the great salmon run in British Columbia; the explosion of sea life in Alaska's coastal waters; and perhaps the greatest marine spectacle on the planet, the annual tide of sardines along South Africa's east coast.
"First published in Great Britain on 2009 by Mitchell Beazley"-- t.p. verso. Companion book to the television series. Includes bibliographical references (p. 315) and index.
Keywords: Natural history; Animal migration; Biological rhythms; Animal populations; Animal behavior; Cycles; Seasons